Editorial: Passion in Human Education - Agnieszka Kaczor; Maria Szymańska (Jesuit University Ignatianum in Krakow, 2023)
Issues related to the passion in upbringing, or education, appear more and more often in the epistemological, empirical and practical space, which indicates its importance for human functioning in the world, for building relationships with self, others, and God. Passion often is  described as a motivating force that dynamize a person to act. It seems to be a factor enabling the man to get the wider knowledge of "Self". It also fosters developing autonomous identity; provokes reflection; strengthens the power of will and commitment in performing different tasks, despite the difficulties that must be overcome, especially, when it concerns harmonious passion (H.P.) - described more extensively in the works of Robert J. Vallerand. Considering the importance of passion in human life, particularly, in educational area,  on behalf of the entire Editorial Boardwe invite our Readers to familiarize themselves with the contents of this issue of Horisons of Education.